2016
DOI: 10.1016/j.bbrep.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Splicing of human chloride channel 1

Abstract: Expression of chloride channel 1 (CLCN1/ClC-1) in skeletal muscle is driven by alternative splicing, a process regulated in part by RNA-binding protein families MBNL and CELF. Aberrant splicing of CLCN1 produces many mRNAs, which were translated into inactive proteins, resulting in myotonia in myotonic dystrophy (DM), a genetic disorder caused by the expansion of a CTG or CCTG repeat. This increase in abnormal splicing variants containing exons 6B, 7A or the insertion of a TAG stop codon just before exon 7 lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…One of the main targets affected by the dysregulated CELF1 is a muscle-specific chloride channel ( CLCN1 ). The splicing pattern of this gene has been deeply characterized by Nakamura et al who revealed that CLCN1 expression is driven via AS by CELF1 among other splicing factors and presents a splice variant carrying a PTC [ 156 ]. The CELF1 gain of function reported in DM induces a switch in the CLCN1 splicing pattern towards a higher fraction of AS RNAs containing a PTC, which deeply downregulates its protein expression [ 157 , 158 ].…”
Section: As-nmd Dysfunction and Associated Human Diseasesmentioning
confidence: 99%
“…One of the main targets affected by the dysregulated CELF1 is a muscle-specific chloride channel ( CLCN1 ). The splicing pattern of this gene has been deeply characterized by Nakamura et al who revealed that CLCN1 expression is driven via AS by CELF1 among other splicing factors and presents a splice variant carrying a PTC [ 156 ]. The CELF1 gain of function reported in DM induces a switch in the CLCN1 splicing pattern towards a higher fraction of AS RNAs containing a PTC, which deeply downregulates its protein expression [ 157 , 158 ].…”
Section: As-nmd Dysfunction and Associated Human Diseasesmentioning
confidence: 99%
“…In this study, we sequenced all coding regions of ATP2A2 in a newly identified patient with DD and BD, and identified a previously reported rare mutation, c.1288‐6A>G, near the splice acceptor site of exon 11 (NM_170665). Furthermore, we investigated the effect of c.1288‐6A>G on splicing, using a minigene splicing assay system . Finally, we performed a literature survey and found a significant enrichment of likely gene‐disrupting mutations among the ATP2A2 mutations found in patients with DD with comorbidity of psychoses.…”
mentioning
confidence: 99%
“…To date, only individual proteins and protein complexes have been investigated in the context of DM1 disease (Forner et al, 2010;Furling et al, 2003;Nakamura et al, 2016), and therefore, there is a notable gap in our understanding of global protein changes in this pathological condition. Although the genetic cause of DM1 is known, a better understanding of the molecular disease processes in animal and human model systems is urgently needed to make progress towards a cure.…”
Section: Introductionmentioning
confidence: 99%
“…To date, mostly only isolated individual proteins and protein complexes have been investigated in the context of DM1 disease (Furling et al, 2003; Forner et al, 2010; Hernández-Hernández et al, 2013; Nakamura et al, 2016) with some exceptions specifically focused on the global proteome changes in neurological context (Sicot et al, 2017; González-Barriga et al, 2021). This leaves a notable gap in our understanding of protein and specifically protein isoform changes in this pathological condition.…”
Section: Introductionmentioning
confidence: 99%